EDUKASI PENINGKATAN KEMAMPUAN BERKOMUNIKASI PADA ANAK CEREBRAL PALSY - Nadia Febrianti Fia; Laelatul Badriah; Kamilah Dwi Lestari; Shiane Hanako Sheba (ABISATYA DINAMIKA ISWARA PUBLISHING, 2026)
Communication skills are fundamental to children’s development, as they enable social engagement, participation in learning, and independence in daily activities. Children with cerebral palsy commonly face communication challenges arising from speech motor limitations, deficits in expressive and receptive language, and complex communication demands, which can adversely influence their overall quality of life. This community-based program was designed to enhance the communication abilities of children with cerebral palsy by providing educational interventions for parents that emphasized speech therapy, Augmentative and Alternative Communication (AAC), and the VI-KN method. The program was implemented at Politeknik Al-Islam Bandung on January 7, 2026, following an educational framework that included preparation, implementation, and evaluation phases. The activities comprised pre-test and post-test evaluations, interactive lectures, AAC demonstrations, practical application of the VI-KN method, and guided discussion sessions. Findings revealed a marked improvement in participants’ knowledge, with mean scores increasing from 40% before the intervention to 90% afterward. Parents also reported greater confidence and improved practical abilities in facilitating their children’s communication at home. In summary, this program effectively strengthened parental knowledge and competencies in supporting communication development among children with cerebral palsy. Future initiatives are recommended to be conducted continuously and expanded through collaborative efforts among families, professionals, and community stakeholders to promote inclusive and community-based rehabilitation. Keywords: cerebral palsy; communication competence; speech therapy; AAC; parent education